Prostate Cancer Tumour Features on Template Prostate-mapping Biopsies: Implications for Focal Therapy [Image: see text] () - Singh, Paras B. (Elsevier Science, 2014)
BACKGROUND: Focal therapy is being offered as a viable alternative for men with localised prostate cancer (PCa), but it is unclear which men may be suitable. OBJECTIVE: To determine the proportion of men with localised PCa who are potentially suitable for focal therapy. DESIGN, SETTING, AND PARTICIPANTS: Our institutional transperineal template prostate-mapping (TTPM) biopsy registry of 377 men from 2006 to 2010 identified 291 consecutive men with no prior treatment. INTERVENTION: TTPM biopsies using a 5-mm sampling frame. OUTCOME MEASUREMENTS AND STATISTICAL ANALYSIS: Suitability for focal therapy required the cancer to be (1) unifocal, (2) unilateral, (3) bilateral/bifocal with at least one neurovascular bundle avoided, or (4) bilateral/multifocal with one dominant index lesion and secondary lesions with Gleason ≤3 + 3 and cancer core involvement ≤3 mm. Binary logistic regression modelling was used to determine variables predictive for focal therapy suitability. RESULTS AND LIMITATIONS: The median age was 61 yr, and the median prostate-specific antigen was 6.8 ng/ml. The median total was 29 cores, with a median of 8 positive cores. Of 239 of 291 men with cancer, 29% (70 men), 60% (144 men), and 8% (20 men) had low-, intermediate-, and high-risk PCa, respectively. Ninety-two percent (220 men) were suitable for one form of focal therapy: hemiablation (22%, 53 men), unifocal ablation (31%, 73 men), bilateral/bifocal ablation (14%, 33 men), and index lesion ablation (26%, 61 men). Binary logistic regression modelling incorporating transrectal biopsy parameters showed no statistically significant predictive variable. When incorporating TTPM parameters, only T stage was a significant negative predictor for suitability (p = 0.001) (odds ratio: 0.001 [95% confidence interval, 0.000–0.048]). Limitations of the study include potential selection bias caused by tertiary referral practise and lack of long-term results on focal therapy efficacy. CONCLUSIONS: Focal therapy requires an accurate tool to localise individual cancer lesions. When such a test, TTPM biopsy, was applied to men with low- and intermediate-risk PCa, most of the men were suitable for a tissue preservation strategy.